Aerobic Growth of Rhodococcus aetherivorans BCP1 Using Selected Naphthenic Acids as the Sole Carbon and Energy Sources - Presentato, Alessandro; Cappelletti, Martina; Sansone, Anna; Ferreri, Carla; Piacenza, Elena; Demeter, Marc A.; Crognale, Silvia; Petruccioli, Maurizio; Milazzo, Giorgio; Fedi, Stefano; Steinbüchel, Alexander; Turner, Raymond J.; et al. (Frontiers in Microbiology, 2018)
Naphthenic acids (NAs) are an important group of toxic organic compounds naturally occurring in hydrocarbon deposits. This work shows that Rhodococcus aetherivorans BCP1 cells not only utilize a mixture of eight different NAs (8XNAs) for growth but they are also capable of marked degradation of two model NAs, cyclohexanecarboxylic acid (CHCA) and cyclopentanecarboxylic acid (CPCA) when supplied at concentrations from 50 to 500 mgL-1. The growth curves of BCP1 on 8XNAs, CHCA, and CPCA showed an initial lag phase not present in growth on glucose, which presumably was related to the toxic effects of NAs on the cell membrane permeability. BCP1 cell adaptation responses that allowed survival on NAs included changes in cell morphology, production of intracellular bodies and changes in fatty acid composition. Transmission electron microscopy (TEM) analysis of BCP1 cells grown on CHCA or CPCA showed a slight reduction in the cell size, the production of EPS-like material and intracellular electron-transparent and electron-dense inclusion bodies. The electron-transparent inclusions increased in the amount and size in NA-grown BCP1 cells under nitrogen limiting conditions and contained storage lipids as suggested by cell staining with the lipophilic Nile Blue A dye. Lipidomic analyses revealed significant changes with increases of methyl-branched (MBFA) and polyunsaturated fatty acids (PUFA) examining the fatty acid composition of NAs-growing BCP1 cells. PUFA biosynthesis is not usual in bacteria and, together with MBFA, can influence structural and functional processes with resulting effects on cell vitality. Finally, through the use of RT (Reverse Transcription)-qPCR, a gene cluster (chcpca) was found to be transcriptionally induced during the growth on CHCA and CPCA. Based on the expression and bioinformatics results, the predicted products of the chcpca gene cluster are proposed to be involved in aerobic NA degradation in R. aetherivorans BCP1. This study provides first insights into the genetic and metabolic mechanisms allowing a Rhodococcus strain to aerobically degrade NAs.